THE EFFICACY OF INVERMECTION IN TREATMENT OF SARCOPTIC MANGE IN GOATS - Hassan , Wahab Amin (The Iraqi Journal of Veterinary Medicine, 2021)
The efficacy of invermection in treatment of an outbreak of mange Moritanin and local adults caused by Sarcoptes Scabiei Var Carprae mites was studied Invermection was given S/C at a dose rate 0.2 mg/kg. body weight twice at an interval of 14 days for 20 infested Moritanin adults and 20 local adults goats. Invermection was 100% effective, and all goats were in good condition after treatment.